Evolution of harmful algal blooms in the East China Sea under eutrophication and warming scenarios. (1st August 2022) - Zhou, Zheng-Xi; Yu, Ren-Cheng; Zhou, Ming-Jiang
Highlights: Blooms of diatom and dinoflagellate in the East China Sea are subject to the impacts of eutrophication and ocean warming. A numerical model is developed based on the competition between diatoms and dinoflagellates. Dinoflagellate blooms will become more frequent with higher peak biomass concentrations. Reducing nitrogen inputs and increasing silicate inputs could prevent further intensification of dinoflagellate blooms. Abstract: Harmful algal blooms (HABs) worldwide are experiencing obvious changes under the combined impacts of global warming, eutrophication, and other driving forces. In the East China Sea (ECS), large-scale blooms caused by dinoflagellates occurred since 2000 and there has been an apparent shift of bloom-causative microalgae from diatoms to dinoflagellates. To predict the future evolution of HABs in this region, a model was developed based on the competition between diatoms and dinoflagellates, which would serve to reproduce the seasonal succession of microalgal blooms driven by multiple environmental factors. The evolution features of HABs were then projected under different scenarios of eutrophication and global warming. Under the 'business as usual' scenario, dinoflagellate blooms are expected to become more frequent with higher peak biomass concentrations over the next 30 years. Changes in nutrient composition of the Changjiang riverine discharge may largely give rise to this phenomenon, and accelerated warming associated with climate change may result in earlier occurrence of dinoflagellate blooms. To prevent further intensification of dinoflagellate blooms, efforts could be made to reduce nitrogen inputs and maintain or even increase silicate inputs from the Changjiang river. Graphical abstract: Image, graphical abstract